The Relative Importance of Academic Activities: Autonomous Values from the Canadian Professoriate - Osakwe, Carlton; Uzoka, Faith-Michael Emeka; Fedoruk, Alan; Gibb, Kalen; Osuji, joseph (Canadian Journal of Higher Education, 2015)
In this paper, we report findings on the contemporary idea of a university as defined by the relative importance of teaching, research, service, and collegiality in teaching-intensive universities. We also investigate Boyer’s model of scholarship relative to the research–teaching–service nexus. Our findings show that while research is embraced as a key academic responsibility of professors, there is general agreement on the primacy of teaching. Equally, awareness of Boyer’s model exposes faculty to diverse opportunities for scholarship and has the potential to open up faculty members to a new idea of the university.